Developmental origins of Parkinson’s disease risk: perinatal exposure to the organochlorine pesticide dieldrin leads to sex-specific DNA modifications in critical neurodevelopmental pathways in the mouse midbrain - Kochmanski, Joseph; Virani, Mahek; Kuhn, Nathan C; Boyd, Sierra L; Becker, Katelyn; Adams, Marie; Bernstein, Alison I (Toxicological sciences, 2024)
Epidemiological studies show that exposure to the organochlorine pesticide dieldrin is associated with an increased risk of Parkinson’s disease (PD). Animal studies support a link between developmental dieldrin exposure and increased neuronal susceptibility in the α-synuclein preformed fibril and MPTP models in adult male C57BL/6 mice. In a previous study, we showed that developmental dieldrin exposure was associated with sex-specific changes in DNA modifications within genes related to dopaminergic neuron development and maintenance at 12 wk of age. Here, we used capture hybridization-sequencing with custom baits to interrogate DNA modifications across the entire genetic loci of the previously identified genes at multiple time points—birth, 6, 12, and 36 wk old. We identified largely sex-specific dieldrin-induced changes in DNA modifications at each time point that annotated to pathways important for neurodevelopment, potentially related to critical steps in early neurodevelopment, dopaminergic neuron differentiation, synaptogenesis, synaptic plasticity, and glial–neuron interactions. Despite large numbers of age-specific DNA modifications, longitudinal analysis identified a small number of differential modification of cytosines with dieldrin-induced deflection of epigenetic aging. The sex-specificity of these results adds to evidence that sex-specific responses to PD-related exposures may underly sex-specific differences in disease. Overall, these data support the idea that developmental dieldrin exposure leads to changes in epigenetic patterns that persist after the exposure period and disrupt critical neurodevelopmental pathways, thereby impacting risk of late-life diseases, including PD.